2017
DOI: 10.4166/kjg.2017.69.4.212
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anti-reflux Therapy on Patients Diagnosed with Minor Disorders of Peristalsis in High-resolution Manometry

Abstract: Background/Aims: Minor disorders of peristalsis are esophageal motility disorders categorized by the Chicago Classification (CC), version 3.0, which was announced in 2014. This study evaluated the efficacy of anti-reflux therapy in patients with minor peristaltic disorders. Methods: Patients with minor peristaltic disorders in accordance with CC v3.0 were included. We reviewed the medical records of patients with esophageal high-resolution manometry findings, and investigated the demographic and clinical infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…An earlier study by our group reported a responder rate of 54.2% for minor peristaltic disorders in patients treated with anti- reflux therapy using PPIs or prokinetics. 23 Since the study was performed retrospectively, the results may vary from those in the current study. In addition, the results of this study are in close agreement with those in previous studies in patients with GERD.…”
Section: Discussionmentioning
confidence: 67%
“…An earlier study by our group reported a responder rate of 54.2% for minor peristaltic disorders in patients treated with anti- reflux therapy using PPIs or prokinetics. 23 Since the study was performed retrospectively, the results may vary from those in the current study. In addition, the results of this study are in close agreement with those in previous studies in patients with GERD.…”
Section: Discussionmentioning
confidence: 67%
“…65 Furthermore, although our results suggest that hypoperistalsis is the main drive for GERD pathophysiology in the LT group, we are unable to ascertain a causative relation between peristaltic vigor and acid exposure due to the retrospective nature, a limitation that is common in studies of similar design. [66][67][68] In conclusion, this is the first study to our knowledge that compares the underlying manometric changes in LT recipients with pH proven acid reflux to matched controls. EGJ barrier function was less impaired with a higher TAPG in LT recipients.…”
Section: Study Limitationsmentioning
confidence: 80%
“… 65 Furthermore, although our results suggest that hypoperistalsis is the main drive for GERD pathophysiology in the LT group, we are unable to ascertain a causative relation between peristaltic vigor and acid exposure due to the retrospective nature, a limitation that is common in studies of similar design. 66 - 68 …”
Section: Discussionmentioning
confidence: 99%